Water use, water use efficiency and drought resistance among warm-season turfgrasses in shallow soil profiles - Zhou, Yi; Lambrides, Christopher J.; Kearns, Ryan; Ye, Changrong; Fukai, Shu (Commonwealth Scientific and Industrial Research Organisation, 2012)
As the available water supply for urban turfgrass management is becoming limited in Australia, it will be crucial to identify drought-resistant turfgrass species and water-saving management strategies. Eight (pre-)commercial turfgrasses grown in Australia, two each of four species including the bermudagrasses (Cynodon dactylon L.), the Queensland blue couches (Digitaria didactyla Willd), the seashore paspalums (Paspalum vaginatum Swartz.) and St Augustinegrasses (Stenotaphrum secundatum (Walt.) Kuntze) were evaluated in two lysimeter experiments. Shallow lysimeters (28 and 40 cm) were used to represent shallow soil profiles typical of urban environments. We measured gravimetric water use for the eight cultivars and calculated water use efficiency (WUE, clipping yield to water use ratio) and WUEr (ratio of WUE under drought to that under irrigated conditions). WUEr measured in both experiments correlated strongly with survival period and this relationship was not affected by soil type or cutting height. Using survival period as the criterion for drought resistance, the best were the bermudagrasses and the worst were the seashore paspalums and Queensland blue couches. The bermudagrass genotypes had the lowest water use, highest WUE and WUEr and the Queensland blue couches and seashore paspalums had the greatest water use, lowest WUE and WUEr. The possible mechanisms of drought resistance included lower water use and lower stomatal conductance as indicated by higher canopy temperature in the early stage of water deficit.